2012
DOI: 10.5923/j.ijas.20120206.02
|View full text |Cite
|
Sign up to set email alerts
|

Health Status of Marginalized Groups in India

Abstract: Marg inalization is a symbol that refers to processes by which individuals or groups are kept at or pushed beyond the edges of society. The term outsiders may be used to refer to those individuals or groups who are marg inalized. This research paper is an endeavour to study the health status of marginalised groups and commun ities -wo men, children, scheduled castes, scheduled tribes, persons with disabilities, mig rants and also the health status of aged in India. The paper also aims to highlight the discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 2 publications
(1 reference statement)
0
9
0
Order By: Relevance
“…Studies indicate that social and economic disparities critically affect the utilization of health services amongst other determinants of maternal health [ 8 , 9 ]. Socially disadvantaged populations are often challenged by long distances to health facilities, poverty, ignorance, and poor health literacy [ 10 , 11 ]. Other studies have shown that woman’s educational attainment, age at marriage, access to livelihood, access to savings, and decision-making power influence the utilization of health services [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that social and economic disparities critically affect the utilization of health services amongst other determinants of maternal health [ 8 , 9 ]. Socially disadvantaged populations are often challenged by long distances to health facilities, poverty, ignorance, and poor health literacy [ 10 , 11 ]. Other studies have shown that woman’s educational attainment, age at marriage, access to livelihood, access to savings, and decision-making power influence the utilization of health services [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…often left out of the scope of general health services in the cities where they work. (Dodd, 2017;Jacob, 2009). The health of the migrants and health issues associated with the migration are major public challenges for the government.…”
Section: Psychiatric Morbidity and Substance Use In Migrant Workers: A Population Based Studymentioning
confidence: 99%
“…A total 51.3% of respondents reported that they were treated unfairly in accessing health services, and 46% were treated unfairly by doctors in health centres. The scavenger community is most prone to stress and other disease, and they are excluded from the health system (Khanday & Akram, 2012;Raksha, 2014).…”
Section: Cultural and Religious Exclusionmentioning
confidence: 99%